'Too smart': Infrastructuring the Internet through regional and rural smart policy in Australia. Issue 1 (25th February 2022) - Randell‐Moon, Holly Eva Katherine; Hynes, Danielle
Abstract: Smart infrastructure is positioned as central to the liveability and viability of rural and regional towns in Australia. The Australian Government's Smart Cities Plan and Regional Connectivity Program includes Smart Investment in regional areas and the New South Wales Government has prioritised connectivity and telecommunications infrastructural development through the Regional Digital Connectivity program. And yet regional and rural communities are typically excluded from the evidence base for smart technologies and services. Local Aboriginal Land Councils are also important stakeholders in managing the digital processes associated with information and infrastructure moving across different Countries. This paper draws on data from the 'It just works!': Regional and rural consumer understandings of smart technologies in North West New South Wales project, including over 130 survey responses and interviews with shire councillors, land councillors, and consumers on smart development and Internet infrastructure in the region. In the areas surveyed, smart regional policy is variously emerging, non‐existent, or assembled from existing policy domains and regulation involving the Internet, telecommunications, regional development, First Nations, and local government. We argue that regional and rural understandings of growth and development are experienced through the infrastructuring processes of Internet quality, availability, and speed.